Komunikasi Pengungkapan Diri (Self Disclosure) Sebagai Resiliensi Mahasiswa Broken Home (Studi Fenomenologi Proses Resiliensi Mahasiswa Broken Home di Surabaya) - Buana, Daya Ning; Dewi, Putri Aisyiyah Rachma (Universitas Negeri Surabaya, 2023)
Broken Homes tend to be synonymous with an incomplete family or a family with divorced parents. Even though a family that has intact members can also be referred to as a